(3eNJUQ MjGI GdMjhGfs - (3Jbi GdOjf eMeO Hf CMeO GdMSjfj GdaGSi GdeGdcjs; (3GdOejQj , ceGd GdOjf CHh GdHbGA eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj, GdOejQj,J (B808 (3g` s
(3ChdgG (B:s
(3hjMedhfg cPdc Edi CQVge s
(3BNQgG (B:s
(3ceG jdhP GdfMd eYShHgG hMSHfG Gddg JYGdi hcai s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B65 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B178s
Keywords: (3GdcjejGA h GdWHjYjGJs